TINJAUAN YURIDIS SENGKETA HASIL PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 BERDASARKAN UNDANG-UNDANG NOMOR 42 TAHUN 2008 TENTANG PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN - Yusridha Putri; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The Constitutional Court has such authority, to decide disputes concerning the results of the general elections and stressed as in Article 24C paragraph (1) of the 1945 Constitution, and further regulated in Law Number 42 of 2008 on the General Election of President and Vice President. Application disputed election results can be filed presented to the Constitutional Court, is only be submitted to the determination of election results set nationally by the Election Commission, which may affect: Determination of Candidate Pair of President and Vice President who entered the second round of general elections of the President and Vice President and election of candidates for President and Vice President to become president and vice president.The purpose of this minithesis, namely: First, to determine the reasons for the applicant to file a dispute results of the elections for president and vice president in 2014. Second, to determine whether the results of the election dispute resolution president and vice president in 2014 in accordance with the Act No. 42 of 2008 on the General Election of President and Vice PresidentOf research and discussion, it can be concluded that the First, basically the reasons the applicant to file a dispute over the results of the General Election of President and Vice President of the Year 2014 is not a dispute over the results of the general election of President and Vice President. because the application is more tend to things that are violations of the general elections of President and Vice President. Second, Dispute Resolution Election Results for President and Vice President 2014 by author normatively incompatible with Law No. 42 Year 2008 regarding the General Election of President and Vice President. However, in this case the dispute over the results of the General Election of President and Vice President of the Year 2014 which was decided by the Constitutional Court has the right material in accordance with the values of the constitution, and the theory of the law states that sovereignty of the people when referring to the principles of the implementation of direct elections , general, free, confidential, honest, and fair.Keywords: Dispute Results - Election - President and Vice President